Algorithm for solving problems related to the natural vibrations of electro-viscoelastic structures with shunt circuits using ANSYS data - Nataliia Iurlova; Natalia Sevodina; Dmitrii Oshmarin; Maksim Iurlov (International Journal of Smart and Nano Materials, 2019)
An algorithm for numerical realisation of a mathematical statement of the natural vibrations problem for electro-viscoelastic bodies with passive external electric circuits (i.e. shunting circuits) with an arbitrary configuration using the finite element method is proposed in the present paper. The proposed algorithm allows considering the viscoelastic properties of materials using the model of linear hereditary viscoelasticity with complex dynamic moduli and is used to solve 3D solid structure problems that are compatible for ANSYS package element types. This technique implies the usage of the global assembled matrices of stiffness and mass, formed in the ANSYS package. The basis of the algorithm is a novel approach that allows performing decomposition of the global assembled stiffness matrix formed in the ANSYS software package into constituents that are needed for calculation of the natural vibration frequencies of the objects under study. These matrix components are used in the program that was written in FORTRAN (Formula Translation) language. This problem could be efficiently applied for analysis of the dynamic processes in smart systems based on piezoelectric materials and could also form a basis for the development of numerical finite element algorithms for optimization of the dissipative characteristics of electromechanical systems with shunted piezoelectric elements.